CORPORATE RESPONSIBILITY IN IMPROVING THE WELL- BEING OF THE WORKFORCE - Ramlan; Rachmad Abduh (Journal of Islamic, Social, Economics and Development, 2023)
The paradigm of development in the field of Labor does need to change, where workers only tend to be seen as a factor of production or part of the commodity must be converted into workers as a whole Indonesian people or as subjects or actors of the production process in development with all dignity and dignity. Between the entrepreneur and the workforce an employment relationship is born. The employment relationship can be held for a certain time as well as an indefinite time. The employment relationship is set forth in an employment agreement that contains a statement of rights and obligations between the parties and their legal consequences. An obligation is a contractual burden or liability. In another sense, duty is something that is duly obliged to be given. The world of employment knows corporate ethics which concerns the relationship between companies and employees as one unit in the corporate environment. For this reason, in order to realize what is labor rights, realize welfare for workers, and realize corporate obligations, employers and workers must understand the labor law that has been regulated.